Penguatan Nilai Al-Islam dan Kemuhammadiyahan Melalui Penerapan Baitul Arqam Bagi Pemuda Muhammadiyah - Saddam Saddam; Iskandar Iskandar; Yudhi Lestanata; Sudarta Sudarta; Rahmad Hidayat; M. Taufik Rachman; Ilham Zitri; Iwin Ardyawin; Rifaid Rifaid; M. Ulfatul Akbar Jafar; Dedi Iswanto; Abdul Sakban; Isnaini Isnaini; Nanang Rahman; Irma Setiawan; Ilham Ilham; Inka Nusamuda Pratama; Hidayatullah Hidayatullah; Adiman Fariadin (Abdimas Mandalika, 2021)
Abstract: Muhammadiyah Youth of Mataram City is committed to printing a cadre of qualified youth, which will contribute positively to the development of the advanced and independent Mataram City Region. As a youth organization, the muhammadiyah youth of Mataram City consistently control social da'wah movements based on culture, middle political movements, and humanitarian movements that touch all levels of society. The purpose of this activity is to increase the value of Al-Islam and Kemuhammadiyahan through the application of Baitul Arqam for Muhammadiyah Youth of Mataram City. Baitul Arqam Pemuda Muhammadiyah Kota Mataram activities were held from October 3-4, 2020 at the Same Hotel Mataram and Batu Layar Hotel. Participants of this activity are 33 members of Muhammadiyah Youth of Mataram City Period 2018-2022. The success of al-Islam and Kemuhammadiyahan value improvement activities through the application of Baitul Arqam for Muhammadiyah youth is seen from the spirit of participants following the activities to the end, the activeness of participants in discussions during the delivery of materials, and many participants said they began to understand further the material that had been delivered in Baitul Arqam.Abstrak: Pemuda Muhammadiyah Kota Mataram berkomitmen untuk mencetak kader pemuda yang berkualitas, yang akan berkontribusi positif terhadap pembangunan Daerah Kota Mataram yang maju dan mandiri. Sebagai Organisasi kepemudaan, pemuda Muhammadiyah Kota Mataram konsisten mengawal gerakan dakwah sosial yang berbasis pada kultural, gerakan politik tengahan, dan gerakan kemanusiaan yang menyentuh seluruh level masyarakat. Tujuan kegiatan ini untuk meningkatkan nilai Al-Islam dan Kemuhammadiyahan melalui penerapan Baitul Arqam bagi Pemuda Muhammadiyah Kota Mataram. Kegiatan Baitul Arqam Pemuda Muhammadiyah Kota Mataram dilaksanakan dari tanggal 3-4 Oktober 2020 di Same Hotel Mataram dan Hotel Batu Layar. Peserta kegiatan ini adalah 33 anggota Pemuda Muhammadiyah Kota Mataram Periode 2018-2022. Kegiatan telah melalui 3 tahapan, yaitu tahapan persiapan, pelaksanaan, dan monitoring dan evaluasi. Keberhasilan kegiatan peningkatan nilai Al-Islam dan Kemuhammadiyahan melalui penerapan baitul arqam bagi pemuda Muhammadiyah terlihat dari semangat peserta mengikuti kegiatan hingga akhir, keaktifan peserta dalam diskusi saat penyampaian materi, dan banyak peserta mengatakan mulai memahami lebih jauh materi yang sudah disampaikan dalam Baitul Arqam.